Популяционный и генетический анализ пищевых предпочтений среди жителей Украины - Тимошина, И.А.; Павиченко, О.В.; Филипцова, О.В. (Фактори експериментальної еволюції організмів, 2015)
Aims. The aim of the study was to perform population analysis of food preferences for sweets, meat, fruit, salty food, the first vegetable dishes, fastfood and fatty food among young people in a sample of Ukraine as well as to evaluate heritability of food preferences. Methods. Genetic analysis was performed taking into account the correlation coefficients for pairs of parent-child (n = 291), siblings (n = 84) and spouses (n = 70). Results. In descending order food preferences of females were located in the following order: sweet, fruits, meat dishes, first vegetable dishes, salty food, fat and fast food. Among males, food preferences in descending order were located as follows: meat dishes, sweet, first vegetable dishes, fruits, fat, fast food and salty food. Genetic analysis showed heritability for first vegetable dishes — 50 %, and heritability for meat — 88 %, fruits — 92 %, salty food — 76 %, sweet and fast food — about 100 %. Conclusions. Sex differences in preferences for sweets, meat, fruit and first vegetable dishes were shown. Genetic analysis showed moderate heritability of food preferences for first vegetable dishes, and high heritability for the rest of food.